Farmworker and nonfarmworker Latino immigrant men in North Carolina have high levels of specific pesticide urinary metabolites. Issue 4 (4th July 2018) - Arcury, Thomas A.; Chen, Haiying; Laurienti, Paul J.; Howard, Timothy D.; Barr, Dana Boyd; Mora, Dana C.; Quandt, Sara A.
ABSTRACT: This article compares detections and concentrations of specific organophosphate (OP), bis-dithiocarbamate, and pyrethroid pesticide urinary metabolites among Latino male farmworkers and nonfarmworkers in North Carolina. Data are from interviews and urine samples collected in 2012 and 2013. Farmworkers and nonfarmworkers frequently had detections for OP and pyrethroid pesticide urinary metabolites. Detection of bis-dithiocarbamate urinary metabolites was less frequent, but substantial among the nonfarmworkers. The concentrations of organophosphate, bis-dithiocarbamate, and pyrethroid pesticide urinary metabolites were high for farmworkers and nonfarmworkers compared to National Health and Nutrition Examination Survey results. Pesticide urinary metabolite detection was not associated with occupation in nonfarmworkers. Research for reducing pesticide exposure among farmworkers remains important; research is also needed to determine pesticide exposure pathways among Latino nonfarmworkers.